The Influence of Hail Protection Net Application on the Yield Capacity and Quality of Eggplant and Pepper in Conditions of Ararat Valley, RA - Tovmasyan, G․ A․; Nazaryan, R․ N․ (ՀԱԱՀ հիմնադրամ)
To obtain high quality and abundant yield product from vegetable crops, it is necessary to improve cultivation technology by applying new agricultural measures and introducing modern agricultural systems, which will allow to obtain competitive products in the market at low costs. Research has been carried out at the ANAU Voskehat experimental farm in 2022. During the research respective eggplant and pepper varieties were cultivated in open field with hail protection net shading. The experimental data showed that net shading had positive effect on the growth, development, quantity and quality of eggplant and pepper yield, providing 45 and 22 c per-hectare yield surplus, respectively.
Keywords: Agronomy and Agroecology